(untitled) (Plant Tissue Culture and Biotechnology, 2015)
Somatic embryogenesis was induced in embryo culture on half MS medium supplemented with NAA (8 mg/l) as the sole plant growth regulator after incubation of the media in the refrigerator at 4°C for two weeks to promote callus induction and somatic embryogenesis in Laurus nobilis. Both embryogenetic calli and somatic embryos were induced in the above selected medium. Embryo growth and development were stimulated by separation of embryos successfully from embryo clusters and transferred onto fresh half MS. Among the selected explants, only leaf bases were found to respond actively to plant regeneration, especially in inducing callus formation and in sustaining faster callus growth. Root formation of regenerated plantlets tended to decrease with time on regeneration media. Overall, 75% of the plantlets derived from the callus survived in the greenhouse; and they all grew to phenotypically normal plants. This procedure will enable the use of regeneration tissue culture technology for germplasm conservation of L. nobilis, a plant of high medicinal and commercial value. Plant Tissue Cult. & Biotech. 24(2): 213-221, 2014 (December)